2019
DOI: 10.22543/7674.62.p253260
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stimulants on eating patterns in children and adolescents with Attention Deficit Hyperactivity Disorder

Abstract: Objectives. This study aims to evaluate the effects of methylphenidate (MPH) on eating patterns and body mass index (BMI) in children with attention deficit/hyperactivity disorder (ADHD). The secondary aim of this study is the comparison between weight and eating behavior of children with ADHD undergoing an MPH treatment, and of children without ADHD. Methods. One hundred fourty three children and adolescents who diagnosed with ADHD were enrolled, and the effects of MPH on the eating patterns and BMI were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These medications may affect appetite, eating patterns and growth. Although stimulants can reduce anthropometric scores (Turan & Akay, 2019), antipsychotics can induce weight gain and, as a side effect, disrupt the gut microbiome, which increase the risk of developing a metabolic disease (obesity, diabetes and cardiovascular disease) (Barton et al, 2020;Bretler et al, 2019). In adults with ASD, and particularly in women, some studies have also reported a higher prevalence of obesity and associated medical conditions, such as dyslipidaemia, diabetes or hypertension, than in populations with TD (Croen et al, 2015).…”
mentioning
confidence: 99%
“…These medications may affect appetite, eating patterns and growth. Although stimulants can reduce anthropometric scores (Turan & Akay, 2019), antipsychotics can induce weight gain and, as a side effect, disrupt the gut microbiome, which increase the risk of developing a metabolic disease (obesity, diabetes and cardiovascular disease) (Barton et al, 2020;Bretler et al, 2019). In adults with ASD, and particularly in women, some studies have also reported a higher prevalence of obesity and associated medical conditions, such as dyslipidaemia, diabetes or hypertension, than in populations with TD (Croen et al, 2015).…”
mentioning
confidence: 99%